2015
DOI: 10.1002/alr.21463
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of surgical margins during endoscopic resection of paranasal sinus malignancy

Abstract: Disease-free status as a function of residual microscopic disease did not prove to be statistically significant. However, positive margins were correlated with a statistically significant increase in regional or distant recurrence. This suggests that complete resection with clear margins can impact oncologic outcomes in patients managed by MIER for sinonasal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A recurrent head and neck malignancy is associated with a generally poor prognosis with a median survival of only 6 to 9 months, and a 2‐year DFS of 36.4% after salvage surgery (early‐stage laryngeal cancer patients excluded) . Patients with recurrent oral cavity, pharynx, and sinonasal malignancies have a 2‐year DFS of 36.2%, 24.6%, and 42%, respectively, after salvage surgery . This study showed a 2‐year DFS of 28% of all tumor locations together.…”
Section: Discussionmentioning
confidence: 64%
“…A recurrent head and neck malignancy is associated with a generally poor prognosis with a median survival of only 6 to 9 months, and a 2‐year DFS of 36.4% after salvage surgery (early‐stage laryngeal cancer patients excluded) . Patients with recurrent oral cavity, pharynx, and sinonasal malignancies have a 2‐year DFS of 36.2%, 24.6%, and 42%, respectively, after salvage surgery . This study showed a 2‐year DFS of 28% of all tumor locations together.…”
Section: Discussionmentioning
confidence: 64%
“…In our cohort, patients with negative surgical margins had increased survival compared with patients who had positive margin, which coincides with other published reports. 17,[19][20][21] This highlights the importance of complete surgical resection with clear margins and may also underscore the benefit of postoperative RT in sinonasal malignancies. In those patients who had positive margins, we did find that patients treated with surgery alone had an increased risk of mortality compared with those who received surgery and adjuvant RT.…”
Section: Discussionmentioning
confidence: 92%
“…12,16,28 Prior studies have demonstrated that failure to achieve local control for SNMM may increase the risk of distant metastasis and death. 29,30 With recent FDA approval and increasing use of several targeted immunotherapy agents for metastatic melanoma, treatment paradigms for sinonasal mucosal melanoma have begun to shift, with several clinical trials investigating their effectiveness in this disease entity. This is the first study in the literature to specifically examine the role of targeted immunotherapy in SNMM, giving attention to local and distant response to treatment.…”
Section: Discussionmentioning
confidence: 99%